Responses of largemouth bass (Micropterus salmoides) to chronic alkalinity stress: Survival, growth performance, physiology, and muscle quality - Xi Shi; Shijie Yuan; Wei Peng; Fengqing Chen; Xiangwei Liu; Xueke Ma; Xiao Ma; Ruwei Xu; Khor Waiho; Xianghui Kong; Cuiyun Lu; Xuejun Li (Aquaculture Reports)
Saline-alkaline water fishery has emerged as a highly promising aquaculture mode in China. To identify potential species suitable for saline-alkaline water aquaculture, this study investigated the effects of different alkalinity stresses (0, 7, 14, 21, 28 mmol/L) on the survival, growth performance, physiology, and muscle quality of largemouth bass Micropterus salmoides. A total of 450 fish (5.58 ± 0.09 g) were randomly allocated to 15 tanks, with three replicates for each group. The experiment lasted for two months. The results indicated that alkalinity stress exhibited no significant impact on the survival rate but significantly reduced growth performance. Compared with the control group, the ALK-28 group exhibited a significantly higher feed conversion ratio and a relatively lower protein efficiency ratio. Physiologically, as alkalinity increased, the concentrations of Na+ and Mg2+, along with the Na+/K+-ATPase and Ca2+/Mg2+-ATPase activities, showed an upward trend. Histologically, alkalinity stress induced some injuries to gills, including gill lamella hyperplasia, abnormal blood cells accumulation, and chloride cells rupture. For muscle nutrition and quality, no significant differences in the nutritional composition and water-holding capacity among treatments were observed. However, ALK-14 significantly enhanced the flavor and nutritional values of amino acids and fatty acids, and ALK-28 significantly improved textural characteristics, including higher hardness, chewiness, and resilience. These results suggested that largemouth bass is a potentially economic candidate species for saline-alkaline water aquaculture because it can survive and show advantages in muscle nutrition and quality under high alkalinity conditions.